A Macro Level Reflection on Practice Teaching and Learning from the west of Ireland. - Kelly, Eleanor; Walsh, Catherine (The Journal of Practice Teaching and Learning, 2023)
This abstract, based on a dialogue across practice and academic contexts explores the anomaly that while it is generally acknowledged that social work placements are integral to professional development and are mainly positive experiences for all concerned, practice teaching remains tangential to social work practice resulting in a chronic shortage of placements. A valuable model of co-production, the paper draws on systems theory to assess and analyse the ongoing precarious situation of placement places in Ireland. The issue is very topical and has potential to generate further discussion and future research.